Increased Body Mass Index Associated with Increased Risky Sexual Behaviors - Gordon, Lonna P. (J Pediatr Adolesc Gynecol, 2015)
STUDY OBJECTIVE: The increasing prevalence of adolescent obesity has led to consideration of the potential effect of obesity on risky sexual behaviors. The current study examined whether body mass index (BMI) was related to age at sexual debut, type of sexual behavior, partner number, and condom use in a population of adolescent women at high risk for obesity and risky sexual behaviors. STUDY DESIGN: Cross-sectional examination of 860 sexually active, predominantly minority, adolescent women who received medical care at an urban health center from 2007 – 2013. INTERVENTION: Self-reported age at sexual debut, types of sexual intercourse, number of partners and condom use was compared to clinically – assessed BMI. RESULTS: Body mass index was positively associated with number of sexual partners (p = 0.001) and history of attempted anal intercourse (p = 0.002). An inverse association was observed with age at first anal intercourse (p = 0.040). CONCLUSIONS: In this sample of adolescent women, increased BMI was associated with riskier sexual practices at a younger age. This study suggests that overweight and obese adolescents are a vulnerable population who may need targeted sexual health counseling.